Degradation of bioabsorbable Mg-based alloys: Assessment of the effects of insoluble corrosion products and joint effects of alloying components on mammalian cells - Grillo, Claudia Alejandra (2015)
This work is focused on the processes occurring at the bioabsorbable metallic biomaterial/cell interfaces that may lead to toxicity. A critical analysis of the results obtained when degradable metal disks (pure Mg and rare earthcontaining alloys (ZEK100 alloys)) are in direct contact with cell culture and those obtained with indirect methods such as the use of metal salts and extracts was made. Viability was assessed by Acridine Orange dye, neutral red and clonogenic assays. The effects of concentration of corrosion products and possible joint effects of the binary and ternary combinations of La, Zn and Mg ions, as constituents of ZEK alloys, were evaluated on a mammalian cell culture. In all cases more detrimental effectswere found for pureMg than for the alloys. Experiments with disks showed that gradual alterations in pH and in the amount of corrosion productswere better tolerated by cells and resulted in higher viability than abrupt changes. In addition, viability was dependent on the distance fromthe source of ions. Experimentswith extracts showed that the effect of insoluble degradation products was highly detrimental. Indirect tests with Zn ions revealed that harmful effects may be found at concentrations ≥150 μMand at ≥100 μM in mixtures with Mg. These mixtures lead to more deleterious effects than single ions. Results highlight the need to develop a battery of tests to evaluate the biocompatibility of bioabsorbable biomaterials.